Sophists and Philosophers in the Roman Empire: an interview with Tim Whitmarsh - Tim; Erlacher, Esdra (Romanitas - Revista de Estudos Grecolatinos, 2026)
Interview with Tim Whitmarsh.
Keywords: Sophists; Philosophers; Roman Empire; Tim Whitmarsh